Detection of bovine rotavirus by RNA electrophoresis - Rasool, N.; Sheikh Omar, Abdul Rahman (Veterinary Association Malaysia, 1989)
A bovine rotavirus exhibiting the group A rotavirus RNA electropherotype was detected in a diarrhoeic faecal specimen obtained from Kluang, Johor in February 1987. All other specimens from the same location and from Kuantan, Pahang, obtained in 1987 and 1988, were negative for rotavirus RNA. The RNA-positive specimen reacted positively in an ELISA test for group A rotavirus.